A Primary-Care Interventional Model on the Diverticular Disease: Searching for the Optimal Therapeutic Schedule. (October 2016) - Campanini, Angelo; De Conto, Umberto; Cavasin, Francesco; Bastiani, Fernanda; Camarotto, Antonio; Gardini, Luigi; Geremia, Alessandra; Marastoni, Cristina; Missorini, Carlo; Quarantelli, Elena; Sassi, Umberto; Scarabello, Francesco; et al.
Abstract : Introduction: In routine colonoscopy, diverticulosis is the most commonly found feature, but only a minority of these cases show symptoms of diverticular disease. From June 2014 to December 2014, we enrolled prospectively 178 patients affected by symptomatic uncomplicated diverticular disease (Male/Female=0.47, mean age 71.7±11.5 y, range 41 to 95 y) from 15 General Pratictioners patient files. All patients were symptomatic; in all cases, diagnosis was been confirmed by a colonoscopy performed at least 1 year before. Patients with acute diverticulitis were excluded. On the basis of the predominant symptoms (abdominal complaints or constipation), patients were addressed to 4 different therapeutic approaches using mesalamine, rifaximine, probiotics (in a consortium of different species of Lactobacillus and Bifidobacterium ), and fibers (Plantago Ovata Husk). All treatments lasted 3 months. Results: Sixty-three patients were enrolled in group A (rifaximine), 43 in group A1 (rifaximine+fibers+probiotics), 23 in group B (mesalamine), and 31 in group B1 (mesalamine+fibers). Analysis of variance suggested a statistically significant difference ( P <0.003) among groups at the end of the observation period, with Groups A1 and B1 showing a higher number of bowel movement per week. Global linear measurement confirmed the role of treatment as a significant factor ( F =2.858; P =0.039) associated with body mass index ( F =6.972; P <0.009). Conclusions: In accordance with the baseline clinical presentation, the supplementation of fiber and/or probiotics is associated with a statistically significant improvement in the clinical pattern of symptoms in patients with diverticular disease in a primary-care/family physician setting.